Analysis of the evolution of the collection of I.P.U. in the town of Páez – Boyacá (2014)
This paper shows a compilation of the process carried out in the municipality of Páez for advancement in the collection of property tax Unified, because such tax is the primary source of tax revenue for the town, it is important to highlight the process done because this ultimately led to an improvement in the resources perceived by this concept, the Unified property Tax is a tax on real property of the owners of the property and has contributed significantly to the income of local authorities